Effectiveness of an Educational Program in Nurses’ Knowledge toward Traumatic Head Injury during Golden Hour at Neurosurgical Hospital - Sabah Abdullah Jaafar1 , Raja Ibrahim Abed 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Globally, traumatic head injury higher mortality rate, and unpredictable outcome. Improvementof nurses’ knowledge of how to deal with early periods of the traumatic head can improve patients outcomes.Objectives: This study aims to assess the effectiveness of an educational program in nurses’ knowledgetoward traumatic head injury during golden hour.Method: A quasi-experimental design was used in this study to assess 50 nurses’ knowledge regardingconstructed educational programs toward traumatic head injury during golden hour who works in criticalcare units in Neuro-surgical hospital. The measurement of the effectiveness of educational program throughthe nurses knowledge includes(54)items concern knowledge related Anatomy of the head and brain;Physiology of intracranial pressure( ICP),cerebral perefusion pressureCPP and blood pressure( BP); Primaryand secondery survey; fluid supply; information about traumatic head injury during golden hour . Reliabilityof instrument was determined through the use of test and retest and the instrument validity was determinedthrough a panel of experts.Results: The study show a comparison significance association between study and control group during pretest and post-test regarding overall assessment, there are improvements in study group knowledge level, thesignificant association for were P= 0.000. For the control group, there is no significant association betweenpretest and post-test P= 0.733 p-value >0.005.Conclusion: The study concludes the current educational program effectively and can improve nursesknowledge in critical care units and recommends to further study assess nurses practice regarding traumatichead injury during golden hour, Adopting an educational program for all nurses and more involved incontinuous education lectures and workshops.